Respuesta :

Answer:

See example below.

Step-by-step explanation:

If the function has the table:

x          f(x)

-3          -6

-2          -4

-1           -2

0            0

Step 1 : Looking at the table, find a pattern. This table f(x) deceases by 2 each time. This is a constant rate of change called slope.

Step 2: Recognize the pattern. Since it is decreasing by 2 each time, this is a linear function. Its equation can be written using y = mx+b.

Step 3: Use the form, y =mx + b and substitute m and b.

Step 4: The slope is m . The slope is -2. m = -2.

Step 5: Find the y-intercept. b is the y-intercept or starting point where x = 0. When x=0, the table shows y=0. So b=0.

This means the rule is y = -2x.